Advances in Communication and Computational Technology Select Proceedings of ICACCT 2019 - Hura, Gurdeep Singh; Singh, Ashutosh Kumar; Siong Hoe, Lau.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book presents high-quality peer-reviewed papers from the International Conference on Advanced Communication and Computational Technology (ICACCT) 2019 held at the National Institute of Technology, Kurukshetra, India. The contents are broadly divided into four parts: (i) Advanced Computing, (ii) Communication and Networking, (iii) VLSI and Embedded Systems, and (iv) Optimization Techniques.The major focus is on emerging computing technologies and their applications in the domain of communication and networking. The book will prove useful for engineers and researchers working on physical, data link and transport layers of communication protocols. Also, this will be useful for industry professionals interested in manufacturing of communication devices, modems, routers etc. with enhanced computational and data handling capacities.
Part 1: Advanced Computing -- Distributed Computing -- Cloud Computing -- Cluster and Grid Computing -- Green Computing -- Image and Video Processing-. Big Data Computing -- Machine Learning -- Parallel Computing -- Soft Computing -- Quantum Computing -- Mobile Computing -- Quantum Computing -- Mobile Computing -- Biomedical Computing, Bioinformatics -- Swarm Intelligence & Swarm Robotics -- Evolutionary Computing -- Cellular Automata -- Cellular Computing -- Membrane Computing -- Part 2: Communication & Networking -- Signal Processing -- Image Processing -- Computer Network -- Wireless Network -- Ad-hoc Network -- Internet of Things (IOT) -- Network Security -- Cryptography -- Physical Layer Security -- Cognitive Radios -- Software Defined Radio -- Optical Communication -- Antenna -- Satellite and Space Communications -- Next Generation Computing and Communication -- Network Analytics -- Vehicular, Underground and Underwater Networks -- RFID and Sensor Network -- Mobile & Ubiquitous Communication Networks -- Mobile Cloud -- Internet Technologies -- Information-Centric Networking -- Remote Sensing and GIS -- Network Protocols -- Modelling & Simulation of Communication Networks and Systems -- Software-Defined Networking -- Fault Tolerance, Reliability, and Survivability -- Flow and Congestion Control -- Network Architectures -- Part 3: VLSI & Embedded Systems -- Computer Architecture -- VLSI Circuit Design and CAD Tools -- Material Science and Nano Technology -- Nano Electronics and VLSI Technology -- Embedded Systems -- Mathematical Modeling and Scientific Computing -- Hybrid Intelligent Models and Applications -- Medical Informatics -- Part 4: Optimization Technique -- Control Systems and Applications -- Renewable Energy -- Power Electronics -- Cloud and Systems Management -- Big Data Communication and Analytics -- Algorithm Heuristic -- Graph, Geometric Algorithms and Applications -- Computer Graphics, Simulation, and Modelling -- Pattern Recognition and Analysis -- Intelligent Image Analysis -- Neuroimaging Techniques -- Robotics and Machine Vision -- Systems and Software Engineering -- Real-time Systems -- Intelligent Control -- Intelligent E-Learning Systems -- Fuzzy Logic -- Artificial Neural Network -- Evolutionary Computation -- Learning Theory -- Probabilistic Methods -- Multimedia -- Text mining -- Social media systems -- Adaptive hypermedia -- Crowd sourcing -- Personalization -- Security, privacy and social impact -- Applications of Computational Intelligence techniques in Science, Engineering, medicine, finance and education etc -- Mechatronics and Robotics.
Keywords: Electrical engineering; Electronic circuits; Signal processing; Image processing; Speech processing systems; Mobile computing; Computational intelligence; Power electronics; Communications Engineering, Networks; Circuits and Systems; Signal, Image and Speech Processing; Mobile Computing; Computational Intelligence; Power Electronics, Electrical Machines and Networks